Leadership during airway management in the intensive care unit: A video-reflexive ethnography study - Brewster, David J.; Butt, Warwick W.; Gordon, Lisi J.; Sarkar, Mahbub A.; Begley, Jonathan L.; Rees, Charlotte E. (Frontiers in Medicine, 2023)
Effective leadership is crucial to team performance within the intensive care unit. This novel study aimed to explore how staff members from an intensive care unit conceptualise leadership and what facilitators and barriers to leadership exist within a simulated workplace. It also aimed to identify factors that intersect with their perceptions of leadership. This study was underpinned by interpretivism, and video reflexive ethnography was chosen as the methodology for the study. The use of both video recording (to capture the complex interactions occurring in the ICU) and team reflexivity allowed repeated analysis of those interactions by the research team. Purposive sampling was used to recruit participants from an ICU in a large tertiary and private hospital in Australia. Simulation groups were designed to replicate the typical clinical teams involved in airway management within the intensive care unit. Twenty staff participated in the four simulation activities (five staff per simulation group). Each group simulated the intubations of 3 patients with hypoxia and respiratory distress due to severe COVID-19. All 20 participants who completed the study simulations were invited to attend video-reflexivity sessions with their respective group. 12 of the 20 participants (60%) from the simulations took part in the reflexive sessions. 142 minutes of video-reflexivity sessions that were transcribed verbatim. Transcripts were then imported into NVivo software for analysis. The five stages of framework analysis were used to conduct thematic analysis of the video-reflexivity focus group sessions, including the development of a coding framework. All transcripts were coded in NVivo. NVivo queries were conducted to explore patterns in the coding. The following key themes to participants conceptualisations of leadership within the intensive care were identified: (1) leadership is both a group/shared process and individualistic/hierarchical; (2) leadership is communication; and (3) gender is a key leadership dimension. Key facilitators identified were (1) role allocation; (2) trust, respect and staff familiarity; and (3) the use of checklists. Key barriers identified were (1) noise and (2) personal protective equipment. The impact of socio-materiality on leadership within the intensive care unit is also identified.